Peran Investasi Asing dalam Mendorong Kompleksitas Ekonomi - Irmawati, Irmawati; Sumardi, Sumardi; Bakhri, Syamsul (Journal of Government Insight, 2024)
This study aims to know the role of investment foreign in pushing a complex economy. The research method qualitative with technique collection data use study References And analysis descriptive in technique analysis the data. Results study This show that investment is the Wrong One factor For increasing the economy in a country. Investment foreign role is important in pushing complex economy Because with increasing complexity economy possible for something country obtain income Which more tall And sustainable in period long. Like the case with an increased rate of growth economy, A little investment in foreign established companies becomes a program of growth and improvement means And infrastructure. A growth high economy​ can become an indicator of a successful country in operating wheel development, Which Finally will used fully for the enhancement of the well-being of its people.